2011
DOI: 10.1016/j.neurobiolaging.2009.09.003
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms underlying basal and learning-related intrinsic excitability in a mouse model of Alzheimer's disease

Abstract: Accumulations of β-amyloid (Aβ) contribute to neurological deficits associated with Alzheimer's disease (AD). The effects of Aβ on basal neuronal excitability and learning-related AHP plasticity were examined using whole-cell recordings from hippocampal neurons in the 5XFAD mouse model of AD. A robust increase in Aβ42 (and elevated levels of Aβ38-40) in naïve 5XFAD mice was associated with decreased basal neuronal excitability, evidenced by a select increase in Ca2+-sensitive afterhyperpolarization (AHP). More… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

16
98
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(115 citation statements)
references
References 83 publications
(116 reference statements)
16
98
1
Order By: Relevance
“…We also found that Na v 1.6 and NR2B are mislocated in APP/PS1, PS1ΔE9, and PS1-M146V neurons. Our conclusions are consistent with the observation that neuronal excitability and synaptic transmission are affected in these animals (35)(36)(37)(38). Remarkably, in the FAD patients associated with PS1, cerebellar dysfunction, including ataxia, Purkinje cell simple spike activity, and mitochondrial transport, occurs before the appearance of Aβ deposition (39).…”
Section: Discussionsupporting
confidence: 92%
“…We also found that Na v 1.6 and NR2B are mislocated in APP/PS1, PS1ΔE9, and PS1-M146V neurons. Our conclusions are consistent with the observation that neuronal excitability and synaptic transmission are affected in these animals (35)(36)(37)(38). Remarkably, in the FAD patients associated with PS1, cerebellar dysfunction, including ataxia, Purkinje cell simple spike activity, and mitochondrial transport, occurs before the appearance of Aβ deposition (39).…”
Section: Discussionsupporting
confidence: 92%
“…In our previous experiments, Ab-induced suppression of BK channels increased cortical excitability , which is consistent with clinical evidence that cortical excitability is elevated in AD patients (Perretti et al, 1996;Ferreri et al, 2003;Inghilleri et al, 2006). In mouse models of Alzheimer's disease as well, the role of hyperexcitability and nonepileptiform activity in the cortex has been a focus of attention as a potentially causative factor in cognitive deterioration (Palop et al, 2007;Driver et al, 2007;Busche et al, 2008;Minkeviciene et al, 2009;Brown et al, 2011), though controversial findings are also reported (Kaczorowski et al, 2011) and the comorbid occurrence of AD and epilepsy is not very frequent. TMS-induced BK channel facilitation in the present study reduced such hyperexcitability and, presumably by this way, contributed to cognitive improvement in 3xTg mice.…”
Section: Discussionsupporting
confidence: 86%
“…Evidence consistent with our finding has also been demonstrated in transgenic mice models of AD (Kaczorowski et al, 2011;Kerrigan et al, 2014;Marcantoni et al, 2014) or aged animals (Pitler and Landfield, 1990;Kumar and Foster, 2002). One possible reason for lower excitability of neurons from Aβ-treated rats could be the augmentation of Ih current in the soma membrane of these channels, as demonstrated by voltage-clamp recording.…”
Section: Enhancement Of Ih Channel Current In Hippocampal Ca1 Pyramidsupporting
confidence: 92%
“…Although, the involvement of voltage-gated and Ca 2+ -dependent potassium channels in the fast AHP has been reported, but it is proposed that Ih channel also could be a strong candidate for modulation of AHP (Kaczorowski, 2011). The role of Ih channel current in the regulation of neuronal excitation through altering the size and kinetics of the AHP has been well documented (Maccaferri et al, 1993;Maccaferri et al, 1994;Poolos et al, 2002;Gu et al, 2005).…”
Section: Enhancement Of Ih Channel Current In Hippocampal Ca1 Pyramidmentioning
confidence: 99%